Rationalizing the pathway to personalized neoadjuvant immunotherapy: the Lombard Street Approach. Issue 2 (24th August 2020) - Versluis, Judith M; Thommen, Daniela S; Blank, Christian U
Abstract : Neoadjuvant chemo(radio)therapy is part of the established standard of care in cancer treatment; neoadjuvant application of immunotherapy, however, is only performed within recent trials. Combination of programmed cell death protein 1 and cytotoxic T lymphocyte antigen 4 blockade shows promising results with high pathologic response rates in the neoadjuvant setting and a very low relapse rate in the responding patients. In addition, neoadjuvant administration allows direct determination of treatment efficacy within the individual patient, and offers easy access to paired tumor material, both pretherapy and post-therapy, thus facilitates the rational development of new combinations driven by preclinical analyses. Patient-derived human tumor explant systems such as a recently developed human patient-derived tumor fragment platform can provide an additional tool to further rationalize the development of new treatment combinations. We will discuss neoadjuvant immunotherapy as a unique opportunity for rational trial design, the development of immune signatures for non-responding patients to steer clinical trial development, and the use of patient-derived ex vivo models to identify new personalized immunotherapy combinations. In this context, we propose the 'Lombard Street Approach', a back and forth approach of characterizing non-responders on neoadjuvant immunotherapy combinations, identifying promising new combinations for this group in the tumor fragment platform, and performing subsequently signature-driven small proof-of-concept combination trials. Repeating this approach with smaller and smaller groups of non-responders will step by step increase the percentage of patients benefiting from neoadjuvant immunotherapy in a rational and fast manner.